Implementation of Base64 and Rot47 Algorithm Combination For Hospital Patient Database Encryption - Iskandar, Dwi; Ismail, Suriana; Pamungkas, Canggih Ajika; Susena, Edy (International Journal of Computer and Information System (IJCIS), 2022)
Abstract—All agency agreed bring data is matter Which very important For protected so that problem security data is matter Which need noticed. Matter Which can done to protect data so that it cannot be misused by others is by use technique cryptography. Cryptography consists of a set of algorithms and techniques For change data become form other so that contents No read and can't explained by Who course that No own authority For read or write data which has been changed. In this study the encryption method used is an algorithm ROT47 to encrypt data where the existing data position will be changed in accordance with amount rotation Which There is, Then data return encrypted use Base64 algorithm which is a scheme of encoding binary data into ASCII code strings in accordance index on Base64. Research results This is Combination ROT47 and Base64 algorithms can be implemented to in system patient database encryption with okAll agency agreed bring data is matter Which very important For protected so that problem security data is matter Which need noticed. Matter Which can done to protect data so that it cannot be misused by others is by use technique cryptography. Cryptography consists of a set of algorithms and techniques For change data become form other so that contents No read and can't explained by Who course that No own authority For read or write data which has been changed. In this study the encryption method used is an algorithm ROT47 to encrypt data where the existing data position will be changed in accordance with amount rotation Which There is, Then data return encrypted use Base64 algorithm which is a scheme of encoding binary data into ASCII code strings in accordance index on Base64. Research results This is Combination ROT47 and Base64 algorithms can be implemented to in system patient database encryption with ok.